Natal origins and timing of migration of two passerine species through the southern Alps: inferences from multiple stable isotopes (δ2H, δ13C, δ15N, δ34S) and ringing data. (21st March 2019) - Franzoi, Alessandro; Bontempo, Luana; Kardynal, Kevin J.; Camin, Federica; Pedrini, Paolo; Hobson, Keith A.
Abstract : Understanding spatial linkages between areas used by migratory animals during the annual cycle is fundamental to their conservation. Stable isotope measurements of animal tissues can be a valuable tool in understanding spatial connectivity and migration phenology of migratory wildlife. We inferred natal origins of two migratory passerines, European Pied Flycatcher Ficedula hypoleuca and European Robin Erithacus rubecula, captured during autumn migration in the Italian Alps, by combining feather δ 2 H ( δ 2 Hf ) and ring recovery data. We used a spatially explicit likelihood‐based method to assign individuals to a precipitation δ 2 H surface calibrated to represent feather δ 2 H, together with the directional probability of origin from ring recoveries. The highest probabilities of origin for most individuals of both species were in central and north‐eastern Europe. Seasonal trends in δ 2 Hf, which described the species' migratory phenology through the Italian Alps, were correlated with feather δ 13 C, δ 15 N and δ 34 S values, indicating strong spatial discrimination related to continental patterns for these isotopes. We demonstrate how this combined information can define catchment areas and migratory connectivity of birds intercepted in the Alps. We highlight the importance of ringing data in defining directional priors to define Bayesian‐based probability surfaces using continental δ 2 Hf isoscapes, and how such information can be used to inform estimates of migratory connectivity.